2006
DOI: 10.1038/sj.bjc.6603389
|View full text |Cite
|
Sign up to set email alerts
|

Familial breast cancer: management of ‘lower risk’ referrals

Abstract: Up to 40% of referrals from primary care to 'breast cancer family clinics' prove to be of women whose assessed risk falls below the guidelines' threshold for management in secondary or tertiary care, despite recommendations that they should be screened out at primary care level. A randomised trial, involving 87 such women referred to the Tayside Familial Breast Cancer Service compared two ways of communicating risk information, letter or personal interview. Both were found to be acceptable to referred women an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 25 publications
(22 reference statements)
2
13
0
Order By: Relevance
“…In a systematic review looking at the uptake of genetic testing and coping strategies of cancer patients, anxiety levels were found to be higher among those who decline to be tested than those receiving genetic test results, either positive or negative, offering an explanation as to why some people may choose not to undergo testing, i.e., as a coping mechanism through avoidance (Case et al 2005). There is also evidence in the wider literature that some individuals found to be at low or average risk resent exclusion from surveillance programs (Young et al 2006) and want their objective risk 'increased' so as to be eligible for screening (Scott et al 2005), supporting some of the evidence in this review. However, and perhaps more reflective of the findings of our review, a meta-analysis of predictors of perceived breast cancer risk and the relationship between perceived risk and breast cancer screening, concluded that it is unclear whether perceived risk influences adherence to BSE (Katapodi et al 2004).…”
Section: Effects Of Perceived Risksupporting
confidence: 71%
“…In a systematic review looking at the uptake of genetic testing and coping strategies of cancer patients, anxiety levels were found to be higher among those who decline to be tested than those receiving genetic test results, either positive or negative, offering an explanation as to why some people may choose not to undergo testing, i.e., as a coping mechanism through avoidance (Case et al 2005). There is also evidence in the wider literature that some individuals found to be at low or average risk resent exclusion from surveillance programs (Young et al 2006) and want their objective risk 'increased' so as to be eligible for screening (Scott et al 2005), supporting some of the evidence in this review. However, and perhaps more reflective of the findings of our review, a meta-analysis of predictors of perceived breast cancer risk and the relationship between perceived risk and breast cancer screening, concluded that it is unclear whether perceived risk influences adherence to BSE (Katapodi et al 2004).…”
Section: Effects Of Perceived Risksupporting
confidence: 71%
“…Similar free-text comments from women at average risk of familial breast cancer are reported by Young et al [20]. Other research has shown that before genetic counselling some women with a family history of breast cancer regarded cancer as an inevitable outcome [17,21].…”
Section: Discussionsupporting
confidence: 54%
“…Around one in four women referred to a breast cancer genetics clinic in the UK do not return their Family History form . These forms, which tabulate information to generate a three‐generation family tree, together with details (site, age of onset and outcome) of any cancers (particularly of breast and ovary) that have occurred among family members are widely used in the practice of breast cancer genetics .…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of completed family history forms often serves as the ‘gateway’ to these services . Some centres have made completion and return of the form a condition of access to the breast cancer family clinic and women who do not comply, after a reminder letter, are referred back to primary care …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation